Relay selection schemes for secure transmission in cognitive radio networks - Al-Jamali, Mukarram; Al-Nahari, Azzam; AlKhawlani, Mohammed (Springer Nature, 2018)
The security in cognitive radio networks (CRNs) has been attracting continuously growing attention due to the open and dynamic nature of cognitive radio architecture. In this paper, we propose new relay selection schemes to improve the physical layer security in CRNs. A trusted decode-and-forward relay is selected to help the secondary user (SU) transmission and improve the secrecy rate in the presence of multiple eavesdroppers and multiple primary users (PUs). The secrecy rate of the SU is characterized under both its own transmit power constraint as well as a set of interference power constraints imposed at each PU, in order to preserve its quality of service. The performance of the proposed schemes is analyzed in terms of the achievable secrecy rate and the intercept probability. Closed form expressions for the asymptotic intercept probability at high source-relays channel variances are also derived. Moreover, new derivations of some existing traditional schemes are presented and compared. The performance comparison of the proposed schemes with the schemes proposed in the literature reveals the superior of the proposed schemes.